DIGESTIBILITY OF LEGUMES 1: EFFECT OF REANS ON ORGANS - H.Mohammadiha; AE.Bender (Tehran University of Medical Sciences, 1980)
While legumes are regarded as good sources of protein they may be poorly digested, so it is useful to determine their digestibility which would give a desirable objective in a breeding programme. In this respect two series of experiments were performed as follow: True digestibility of the nitrogen (TND) of cooked white haricot beans (phaseolus vulgaris) was measured by feeding it to rats at 20,40, and 80% levels in the diet, and 20% protein), for 10 days period. The animals used were 23 days and 63 days old. The results show TND at three mentioned dietary levels 80, 74, and 67 for young animals and 63, 55, and 51 for more mature animals. At the end of each experiment selected organs of rats dissected and weighed. The result indicated that length of small intestine was greater in bean fed rats. While heart and pancreas did not show any weight increment, liver's weight was 20% heavier in the 80% bean fed animals in comparison to non-protein and stock diet fed rats.